The effects of intergenerational income mobility and per pupil education spending on economic growth - Joseph A. Mauro (Cogent Economics & Finance, 2025)
Intergenerational income mobility is often studied in the context of inequality, but it also plays a critical role in long-term economic development. This study introduces an endogenous growth model to explore how intergenerational income mobility affects macroeconomic growth. In the model, individuals earn wages based on their education and skills, with the accumulation of human capital influenced by inherited abilities, as well as public and private educational investments. A key finding is that economies that allocate more resources to primary and secondary education achieve higher levels of both absolute and relative income mobility, signaling a better alignment of individuals with suitable occupations. This increased mobility, in turn, drives greater economic growth and higher educational attainment. The results highlight intergenerational mobility as a crucial factor for economic growth, providing valuable insights for public policy design.